Farm management information system (Crop planning and tracking modules) - Leng, Kai Yi (2023)
The purpose of the Farm Management System is to automate the existing manual system with the assistance of computerized equipment and full-fledged computer software. Therefore, by using farm management system, it will help users to optimize and manage farm activities and production activities. This project will develop a mobile based farm management application which allows user to plan, monitor and analyse all activities on the farm easily. It allows important data and information to be stored for a longer period of time with easy access. This project will focus on helping user to plan farm activities efficiently. It is important for farmer to have a better planning on the farmland because farm plan can maximize the resource use efficiency at the farm. The development tool that is used is Flutter with Dart language. Besides, the hardware will be used for the project is laptop. The final product of the project is the combination of using Google Maps, application programming interface (API), Firebase and an Android mobile application with the ability to plan and monitor farm activities and detect pests and diseases.